(*3 both sides)
(-12 both sides) <--- not -4 as you suggest, so this may be where you went wrong
Its another transposition of formulae question that dosen't seem to be sinking in
Make x the subject:
5(3 - x/3) = 4(x/2 + 1) The solution should be x=3
I could only simplify it before loosing the plot
simplified to 15 - 5x/3 = 2x + 4....then tried multiplying both sides by 3, adding 5x and taking away 4 ending up with 11=11x which is obviously wrong.....would appreciate being told where I'm going wrong.